ICT Business Centre to enhance it sharing and knowledge - UMP, PNC
Universiti Malaysia Pahang (UMP) Vice-Chancellor, Professor Dato’ Dr. Daing Nasir Ibrahim launched the ICT Business Centre in a move to boost the sharing of knowledge and skills in information technology (IT) that would benefit the community as well.